2010
DOI: 10.1016/j.physe.2010.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states and transport properties in the Kronig–Penney model with correlated compositional and structural disorder

Abstract: We study the structure of the electronic states and the transport properties of a Kronig-Penney model with weak compositional and structural disorder. Using a perturbative approach we obtain an analytical expression for the localisation length which is valid for disorder with arbitrary correlations. We show how to generate disorder with self-and cross-correlations and we analyse both the known delocalisation effects of the long-range self-correlations and new effects produced by cross-correlations. We finally … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…As for cross-correlations, they can either enhance or reduce the opacity of the low-transmittivity intervals. Numerical studies confirmed these expectations [20]. They also showed that the effects of self-and cross-correlations can be detected in random samples of moderate size, as can be seen in figure 2, which represents the transmission coefficient T of a random Kronig-Penney model of N = 40 sites for a specific realization of the disorder.…”
Section: Theoretical Considerationssupporting
confidence: 57%
See 2 more Smart Citations
“…As for cross-correlations, they can either enhance or reduce the opacity of the low-transmittivity intervals. Numerical studies confirmed these expectations [20]. They also showed that the effects of self-and cross-correlations can be detected in random samples of moderate size, as can be seen in figure 2, which represents the transmission coefficient T of a random Kronig-Penney model of N = 40 sites for a specific realization of the disorder.…”
Section: Theoretical Considerationssupporting
confidence: 57%
“…The weak-disorder case is identified by the conditions [18][19][20] with n = a n+1 − a n representing the relative displacement of two contiguous barriers. If disorder is weak, one can obtain an analytical expression for the localization length l loc of the electronic states ψ of the model (1) [18][19][20]. Following the Hamiltonian map approach, one can show that, within the second-order approximation, the electronic states have an inverse localization length equal to…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[52]). An analytical expression for the inverse localisation length (22) was derived for the case of weak disorder in [53][54][55]. As shown in [53], disorder can be considered weak provided that…”
Section: Infinite Aperiodic Kronig-penney Modelmentioning
confidence: 99%
“…It is possible to construct sequences of self-and cross-correlated random variables u n and Δ n such that the corresponding power spectra(25) vanish over pre-defined intervals. A way to produce such sequences was presented in [55]; for the sake of completeness, we outline the main steps in appendix B.…”
Section: Infinite Aperiodic Kronig-penney Modelmentioning
confidence: 99%